Efficacy and toxicity of oxidative disinfectants for the removal of gill amoebae from the gills of amoebic gill disease affected Atlantic salmon (Salmo salar L.) in freshwater - Powell, MD; Clark, GA (2004)
Amoebic gill disease (AGD) of Atlantic salmon is treated commercially by bathing affected fish in freshwater. Recently, the efficacy of freshwater bathing has been questioned, and the aim of this study was to examine the potential for improving bathing efficacy using additives to the freshwater bath. AGD-affected Atlantic salmon were bathed in 350 L tanks containing oxygenated freshwater to which chlorine dioxide (0-50 mg L-1), chloramine-T (0-50 mg L-1) or hydrogen peroxide (0-100 Î¼L L-1) was added. Before and following a 3-h exposure to the freshwater and chemical additive, the gills were removed from a sub-sample of fish and the number of live amoebae on the gills were counted and smears made for confirmation of the presence of Neoparamoeba pemaquidensis, the causative agent of AGD. Following a further 3-h exposure, a sub-sample of fish was bled from the caudal vein and the gills were removed for histological examination. Chlorine dioxide and chloramine-T at 25-50 and 10-50 mg L-1, respectively, reduced the number of amoebae on the gills by approximately 50% compared with pre-exposure numbers. The results from hydrogen peroxide treatment were equivocal and the toxicity of hydrogen peroxide was high. The toxicity of chlorine dioxide varied with freshwater hardness and/or suspended solid load, whereas chloramine-T toxicity was low, with mortalities attributable only to elevated temperatures at the highest concentration tested. In conclusion, chlorine dioxide and chloramine-T show promise as potential freshwater additives for the improved removal of N. pemaquidensis and possibly, other amoebae from the gills of commercially farmed Atlantic salmon.